Transcriptome analysis reveals the mechanism of the effect of flower tea Coreopsis tinctoria on hepatic insulin resistance. Issue 11 (29th October 2018) - Jiang, Baoping; Lv, Qiuyue; Wan, Wenting; Le, Liang; Xu, Lijia; Hu, Keping; Xiao, Peigen
Abstract : Non- Camellia tea and herbal medicine help prevent the development of diabetes and other metabolic diseases. Abstract : Non- Camellia tea and herbal medicine help prevent the development of diabetes and other metabolic diseases. Previous studies revealed that Coreopsis tinctoria (CT) flower tea increases insulin sensitivity and, in some high-fat diet (HFD)-fed rats, even prevents hepatic metabolic disorders. However, the molecular mechanisms by which CT improves insulin resistance are not known. In this study, six-week-old rats were fed a normal diet (ND), an HFD or an HFD supplemented with CT for 8 weeks. Serum samples were collected, and the livers were extracted for RNA-seq gene expression analysis. Real-time PCR and western blotting further verified the RNA-seq results. In our results, dietary CT ameliorated HFD-induced hepatosteatosis, glucose intolerance, and insulin resistance. In the HFD group, 1667 differentially expressed genes (DEGs) were identified compared with the ND group. In the CT group, 327 DEGs were identified compared with the HFD group. Some of these DEGs were related to insulin signalling, hepatic lipogenesis and glucose homeostasis. This study suggested that insulin resistance with hyperinsulinaemia, and not insulin insufficiency, is an early problem in HFD-fed rats, and CT downregulates insulin secretion genes ( e.g., Rasd1, Stxbp1 and Sfxn1 ). Hepatic gene and protein expression analyses indicated that the regulatory effects of CT on glucose and lipid homeostasis are likely mediated via the Akt/FoxO1 signalling pathway and are regulated by the transcription factors hairy and enhancer of split 1 (HES1) and small heterodimer partner (SHP). Our study provides transcriptomic evidence of the complex pathogenic mechanism involved in hepatic insulin resistance and proves that supplementation with CT improves insulin resistance at a global scale.